Findings from a three-round Delphi study: essential topics for interprofessional training on complementary and integrative medicine - Homberg, Angelika; Klafke, Nadja; Loukanova, Svetla; Glassen, Katharina (BMC complementary medicine and therapies, 2020)
Integrating complementary medicine into medical care promotes patient-oriented care. A well-informed and collaborative professional healthcare team is essential for effective and patient-safe implementation of these methods. At present, the skills for patient counseling, therapy and care regarding complementary medicine vary among the professional groups involved. Professionals generally feel that they are not sufficiently qualified in this area. Curricular concepts for Complementary and Integrative Medicine (CIM) are virtually non-existent in undergraduate interprofessional training. The aim of this study is to initiate a consensus-building process between various experts (professionals, students, patient and faculty representatives) in order to identify which topics should be the focus of such a curriculum.
Gesehen am 10.12.2020